Defining and Managing for Healthy Vineyard Soils, Intersections With the Concept of Terroir - Lazcano, Cristina; Decock, Charlotte; Wilson, Stewart G. (Frontiers in Environmental Science, 2020)
The use of sustainable soil management practices is becoming common in wine growing regions around the world in response to an increased awareness of the value of soil health to maintain, environmental quality, crop yield and grape quality. In spite of this, little information is available on the meaning of soil health within a viticultural context, the effects of soil management practices on soil health and the consequences for grape quality and the expression of the terroir. In this review we discuss interrelated dynamic physical, chemical and biological properties associated with soil health and how they could be important in the expression of the terroir. We focus on the use of cover crops and compost application, two practices commonly used in vineyard soils, and how they affect these physical, chemical and biological aspects of soil health, grape quality and the expression of the terroir. Finally, we discuss research gaps, and best management practices to reduce possible tradeoffs associated with these practices such as the emission of greenhouse gasses.